Eudragit ® FS 30 D polymeric films containing chondroitin sulfate as candidates for use in coating seeking modified delivery of drugs - Camila Borges dos Reis; Daniele Schaab Boff; Isabela Angeli de Lima; Leandro Freire dos Santos; Osvaldo Albuquerque Calvalcanti; Élcio José Bunhak
ABSTRACT Polymeric films associating different concentrations of Eudragit(r) FS 30 D (EFS) and chondroitin sulfate (CS) were produced by casting for the development of a new target-specific site material. Formed films kept a final polymer mass of 4% (w/v) in the following proportions: EFS 100:00 CS (control), EFS 95:05 CS, EFS 90:10 CS and EFS 80:20 CS. They were analyzed for physical and chemical characteristics using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and Raman spectroscopy. Furthermore, they were characterized by their water vapor permeability and degree of hydration at different conditions simulating the gastrointestinal tract. No chemical interactions were observed between CS and EFS, suggesting only a physical interaction between them in the different combinations tested. The results suggest that EFS and CS, when combined, may form films that are candidates for coating processes seeking a modified drug delivery, especially due to the synergism between pH dependency and specific biodegradability properties by the colonic microbiota. EFS 90:10 CS proved to be the most suitable for this purpose considering hydration and permeability characteristics of different associations analyzed.